La diffusion d’Ébola dans les pays de la Mano River : approche géographique - Hélène Simon-Lorière; Benjamin Lysaniuk (EchoGéo)
The magnitude of the actual Ebola outbreak is unprecedented in the history of this disease discovered in 1976. Affecting mainly the Mano River countries (Guinea, Liberia and Sierra Leone), the epidemic has rapidly circulated in the region from the initial point of Gueckedou (Guinea). By questioning the Ebola pathogenic complex, the recent history of migrations induced by years of conflict and the spatial organization of cities and communication routes, we show that a geographical approach can be relevant to formulate credible hypotheses explaining the spread of Ebola in the considered region.